Stem cells in craniofacial development and regeneration - Huang, George T.-J; Thesleff, Irma (Wiley-Blackwell, 2013)
Stem Cells, Craniofacial Development and Regeneration is an introduction to stem cells with an emphasis on their role in craniofacial development. Divided into five sections, chapters build from basic introductory information on the definition and characteristics of stem cells to more indepth explorations of their role in craniofacial development. Section I covers embryonic and adult stem cells with a focus on the craniofacial region, while sections II-IV cover the development and regeneration of craniofacial bone, tooth, temporomandibular joint, salivary glands and muscle. Concluding c.